2020
DOI: 10.2147/dmso.s223929
|View full text |Cite
|
Sign up to set email alerts
|

<p>Individual and Combined Components of Metabolic Syndrome with Chronic Kidney Disease in Individuals with Hypertension and/or Diabetes Mellitus Accompanied by Primary Health Care</p>

Abstract: Purpose: To identify the associations between MetS and its components and chronic kidney disease (CKD) in a population with arterial hypertension (AH), or diabetes mellitus (DM) accompanied by the Primary Health Care (PHC). Patients and methods: A cross-sectional study with 788 individuals diagnosed with AH and/or DM followed by PHC of Viçosa, Brazil. Anthropometric, biochemical and clinical measures were performed for the diagnosis of MetS and CKD. MetS was identified using the NCEP-ATPIII criteria. CKD was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The data used in the present study stems from the project entitled: "Prevention of diseases and illnesses in patients with arterial hypertension in the context of Primary Health Care: chronic kidney disease in focus" [8]. This is a cross-sectional study with a representative sample of hypertensive and/or diabetic individuals with no previous diagnosis of chronic kidney disease, receiving PHC in a city in the southeastern region of Brazil, carried out from August 2017 to April 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The data used in the present study stems from the project entitled: "Prevention of diseases and illnesses in patients with arterial hypertension in the context of Primary Health Care: chronic kidney disease in focus" [8]. This is a cross-sectional study with a representative sample of hypertensive and/or diabetic individuals with no previous diagnosis of chronic kidney disease, receiving PHC in a city in the southeastern region of Brazil, carried out from August 2017 to April 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Components of MS, including HTG, HFPG and HBP, AO, and LHDL-C, were found to be associated with CKD, consistent with previous findings. 12 , 19–21 Non-communicable diseases such as obesity, 18 , 22 , 23 hypertensive disease 24–26 diabetes 27 , 28 and hyperuricemia 26 are also risk factors for CKD. It is unclear whether insulin resistance is an independent predictor of CKD mortality and cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study included relatively young participants (aged 20 and over) while the present study is more meaningful for formulation of prevention and treatment measures for chronic non-communicable diseases among the middle-aged and elderly in Southern China. In a cross-sectional study of 788 patients diagnosed with hypertension or diabetes in Brazil, 12 MS was defined using NCEP-ATPIII standards. The results showed that MS and its single or combined components were independently associated with CKD and were highly consistent with the present results.…”
Section: Discussionmentioning
confidence: 99%
“…The study is part of a larger project 7 , which followed the ethical precepts of Resolution 466/2012 of the National Health Council, being approved by the Ethics Committee of the Federal University of Viçosa (Opinion: 1203. 173, CAAE: 47356115.3.…”
Section: Methodsmentioning
confidence: 99%